The Development of Heyzine Flipbook-Based Interactive E-Book in Arabic Language Learning at Madrasah Aliyah - Febrizka, Karina; Rahmawati, Rahmawati; Hanomi, Hanomi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The rapid development of digital technology, especially in the world of education, has driven changes in the provision and use of teaching materials, starting from conventional print media to more interactive and easily accessible digital learning resources. This study aims to develop an interactive e-book based on Heyzine Flipbook media. This study uses a development research method with the ADDIE development model. The teacher needs analysis showed a score of 84.4%, for the student needs analysis showed a score of 80.4%, both indicating that teachers and students